2022
DOI: 10.3389/fpsyg.2022.921250
|View full text |Cite
|
Sign up to set email alerts
|

Family cohesion, shame-proneness, expressive suppression, and adolescent mental health—A path model approach

Abstract: ObjectiveThe family remains one of the most important relationship systems into early adulthood and provides an important foundation for lifelong mental health. Dysfunctional family cohesion can promote adjustment problems in adolescents and might also affect adolescents’ self-concept and strategies for coping with emotional distress. To test these relationships and the underlying mechanisms, we proposed a dual mediation model describing the associations between family cohesion and internalizing and externaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 131 publications
(170 reference statements)
0
5
0
Order By: Relevance
“…Finally, our research revealed that parents' cognitive reappraisal plays a crucial role in ameliorating children's emotional difficulties and hyperactivity-inattention symptoms, while parents' expressive suppression is primarily associated with heightened hyperactivity-inattention symptoms. This seems to suggest that a greater utilization of adaptive emotion regulation strategies, such as cognitive reappraisal, within the parental context can promote a family environment that fosters the open expression of emotions and facilitates effective communication among family members [16]. Such an environment is linked to improved psychological outcomes, as it serves to mitigate emotional and behavioral challenges in both parents and children [16] and enhances their ability to cope with issues related to illness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, our research revealed that parents' cognitive reappraisal plays a crucial role in ameliorating children's emotional difficulties and hyperactivity-inattention symptoms, while parents' expressive suppression is primarily associated with heightened hyperactivity-inattention symptoms. This seems to suggest that a greater utilization of adaptive emotion regulation strategies, such as cognitive reappraisal, within the parental context can promote a family environment that fosters the open expression of emotions and facilitates effective communication among family members [16]. Such an environment is linked to improved psychological outcomes, as it serves to mitigate emotional and behavioral challenges in both parents and children [16] and enhances their ability to cope with issues related to illness.…”
Section: Discussionmentioning
confidence: 99%
“…This seems to suggest that a greater utilization of adaptive emotion regulation strategies, such as cognitive reappraisal, within the parental context can promote a family environment that fosters the open expression of emotions and facilitates effective communication among family members [16]. Such an environment is linked to improved psychological outcomes, as it serves to mitigate emotional and behavioral challenges in both parents and children [16] and enhances their ability to cope with issues related to illness. Conversely, the use of maladaptive strategies, such as emotional suppression, particularly in the context of chronic disease [38], is linked to unfavorable psychological outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Families that are disengaged have strong limits between their members and show minimal emotional bonds and interactions among them [ 15 , 16 ]. Wark et al (2003) [ 17 ] assumed that increased levels of family disengagement could be connected to emotional neglect as a type of child maltreatment; and hypothesized that emotional child neglect would be related to lower levels of balanced cohesion and adaptability and would be associated with higher levels of psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the educational environment ( Tripon et al, 2023 ), family is also an important foundation of adolescent psychological well-being (e.g., Li et al, 2022 ; van Eickels et al, 2022 ). Different family functioning models such as Cox and Paley’s (1997) family systems theory and Conger et al’s (1994) family stress model of economic hardship support the conjecture that favorable family functioning promotes the well-being of adolescents ( Stewart et al, 2022 ; Zhu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%